COMPARATIVE PHONETICS OF UKRAINIAN AND SPANISH LANGUAGES: DIFFICULTIES FOR UKRAINIAN-SPEAKING STUDENTS - Bratel, Olena; Popova, Olena (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article examines the phonetic features of Spanish and Ukrainian languages, focusing on the difficulties Ukrainian-speaking students face when learning Spanish pronunciation. The study highlights specific phonetic challenges arising from the differences between the phonetic systems of both languages. To address these challenges, a hierarchy of sound difficulty is proposed to aid the learning process. The research is based on a comparative analysis of Spanish and Ukrainian phonetic systems, offering practical insights for teachers to improve pronunciation instruction. The developed hierarchy serves as a tool for optimizing phonetic training and enhancing the effectiveness of Spanish language education for Ukrainian speakers.________________References:• Gavrilova, O. V., & Gnatisheva, O. O. (2024). Distanciini metody ta pryjomy navchannia fonetyky anhliiskoi movy [Distance methods and techniques of teaching English phonetics]. Innovatsiina pedahohika [Innovative Pedagogy], 71(1), 41–45.• Dubchak, O. (2020). Chuty ukrainskoiu. U sviti zvukiv i bukv [Hearing Ukrainian. In the world of sounds and letters]. Kyiv: Vikhola.• Komarova, Z. I., & Rozgon, V. V. (2014). Suchasna ukrainska literaturna mova: fonetyka, orfoeppiia, hrafika, orfohrafiia [Modern Ukrainian literary language: Phonetics, orthoepy, graphics, orthography]. Uman: FOP Zhovtyi O. O.• Bihych, O. B., Borysko, N. F., Boretska, H. E., et al. (2013). Metodyka navchannia inozemnykh mov i kultur: teoriia i praktyka [Methodology of teaching foreign languages and cultures: Theory and practice] (S. Yu. Nikolaieva, Ed.). Kyiv: Lenvit.• Pyskach, O. D., & Hotsa, E. D. (2022). Suchasna ukrainska mova: Fonetika. Fonolohiia. Orfoeppiia [Modern Ukrainian language: Phonetics. Phonology. Orthoepy]. Uzhhorod.• Moisiienko, A. K., Bas-Kononenko, O. V., Bondarenko, V. V., et al. (2010). Suchasna ukrainska literaturna mova: Leksykolohiia. Fonetyka [Modern Ukrainian literary language: Lexicology. Phonetics]. Kyiv: Znannia.• Tarnopolskyi, O. B., & Kukharenko, A. A. (2015). Pedahohichne zistavlennia movnykh system ispanskoi ta anhliiskoi mov yak linhvistychnie pidgruntia navchannia u vyshi ispanskoi movy yak druhoi inozemnoi na osnovi anhliiskoi yak pershoi inozemnoi [Pedagogical comparison of the language systems of Spanish and English as a linguistic basis for teaching Spanish as a second foreign language at the university on the basis of English as a first foreign language]. Visnyk Zhytomyrskoho derzhavnoho universytetu imeni Ivana Franka [Bulletin of Zhytomyr Ivan Franko State University], 3(81), 24–28.• Cerda Masso, R. (2000). Fonología funcional del español. In Introducción a la Lingüística española (pp. 139–153). Barcelona: Ariel.• Gil, J., & Llisterri, J. (2004). Fonética y fonología del español en España (1978–2003). Lingüística Española Actual, 26(2), 5–44.• Llorach, E. A. (2001). Gramática de la lengua española. Fonología. Madrid.• Topal, İ. H. (2019). CEFR-oriented probe into pronunciation: Implications for language learners and teachers. Journal of Language and Linguistic Studies, 15(2), 420–436.
Keywords: phonetics, Spanish language, Ukrainian language, pronunciation, difficulties, comparative analysis